Screen Printing the Glassware as Souvenir to Increase Selling Value and Income on Handicraft Group in Karangrejo, Jember, East Java - Ilham Saifudin; Nurhalimah Nurhalimah (Kontribusia : Research Dissemination for Community Development, 2019)
Glasses / mugs and plates have a function as tableware, it also has a function as souvenirs that we can adjust to the desired character and look attractive, so that it has high value to sell. The method used to make souvenirs of glasses / mugs and plates is by means of a screen printing technique with digital printing. Screen printing techniques with digital printing on glasses / mugs and plates are done by a press machine, so that they can be decorated by using names, images according to the desired order. The development of souvenirs of glasses / mugs and plates in Jember is still rarely found. It can be proved, in each shop there are only a few which sell it, but are not produced by themselves. This has become an attractive and beneficial business opportunity for the economic development of the Handycraft Group and the Sekar Kartini Women's Cooperative members whose businesses have been declining recently. Thus, the specific target to be achieved is the establishment of a business unit for souvenirs of character glasses / mugs and plates by using appropriate technology, namely screen-printing presses and digital printing, and marketing management with the help of information technology (social media).